From Robots to Social Robots. Trends, Representation and Facebook Engagement of Robot-Related News Stories Published by Italian Online News Media - Righetti, Nicola; Carradore, Marco (Italian Sociological Review, 2019)
In recent decades, robots, social robots and artificial intelligence have increasingly entered daily life, affirming their presence not only in traditional spheres such as industrial production, but also gaining access to social reproduction, expressive functions and domestic activities. Considering the social relevance robots have now acquired, this essay aims at investigating their cultural representations in Italian online news media. More specifically, the study investigates trends of robot-related topics in online newspaper coverage and Facebook engagement over time, and analyzes news topics through text mining techniques. The study relies on a dataset of about 3,000 news stories published between 2014 and 2018 by some 100 different Italian news media. Results show a constant increase in news relating to robots, a major interest in work issues and a thematic shift over time: more recent topics describe the social-reproduction functions of robots. Finally, some suggestions for future research are outlined.